Distributional analyses of word frequency effects in Chinese sentence reading and lexical decision tasks. (3rd October 2018) - Ma, Guojie; Zhuang, Xiangling
Abstract : Previous studies used the ex‐Gaussian fitting technique to examine the distribution of word frequency effects in English sentence reading and lexical decision tasks. It was found that word frequency influences reaction times and eye fixation durations by both shifting the distribution to the right and increasing the skew for the low‐frequency target words. We used the same method to examine the distributional effects of word frequency through a Chinese sentence reading task in Experiment 1 and a lexical decision task in Experiment 2. Experiment 1 showed that word frequency only significantly influenced rightward skew for first fixation duration, while Experiment 2 showed that word frequency influenced reaction times by both shifting the distribution to the right and increasing the skew. Our data reveal both similarities and differences between Chinese and English word recognition on the distributional level, which has certain theoretical implications for modelling Chinese reading. Highlights: What is already known about this topic? Both reaction times and eye fixation times can be well fit by ex‐Gaussian distribution in English word recognition. Word frequency influences reaction times and eye fixation durations by both shifting the distribution to the right and increasing the skew for the low‐frequency target words in reading English texts. What this paper adds? We used this method to examine the distribution of word frequency effects in Chinese sentence reading and lexical decision tasks. Word frequency influenced average fixation durations only by increasing the degree of skew; however, word frequency influenced average reaction times by both shifting the distribution to the right and increasing the degree of skew in reading Chinese texts. Implications for theory, policy or practice? The present study has certain theoretical implications on modelling Chinese reading. The model of Chinese reading should simulate how lexical variables influence eye fixation duration on the distributional level.